The Effect of Family Environment, World of Work Knowledge, and Work Motivation on Mental Work Readiness of Vocational School Students in East Lombok - Heny Fikri Rahman; Sutiman Sutiman; Andi Nuralfiah; Laely Ngaenatul Wardah Isnaeni; Arman Arman; Alia Rakhmawati (Journal of Vocational Education Studies, 2026)
This study investigates the effects of family environment, knowledge of the world of work, and work motivation on the mental work readiness of vocational high school students in East Lombok. Employing an ex post facto design, the study targeted all grade XI vocational schools in the region offer engineering programs that encompass TKR, Ototronik, TSM, and Heavy Equipment. A total of 196 students were selected through proportional random sampling to ensure representative distribution across schools. Data were collected via structured questionnaires and analyzed using descriptive statistics, simple regression, and multiple regression in SPSS. The findings reveal: (1) a significant effect of family environment on work readiness (r = 0.618, R² = 0.382, p < 0.001); (2) a significant effect of knowledge of the world of work on work readiness (r = 0.782, R² = 0.611, p < 0.001); (3) a significant effect of work motivation on work readiness (r = 0.694, R² = 0.481, p < 0.001); and (4) a combined influence of family environment, knowledge of the world of work, and work motivation on work readiness (R = 0.832, R² = 0.693, p < 0.001). These results underscore the critical role of both internal and contextual factors in shaping students’ preparedness for the workforce.